2003
DOI: 10.1088/0953-8984/15/47/001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of transition and noble metal vicinal surfaces: energetics, vibrations and stability

Abstract: The energetics of transition and noble metal (Rh, Pd, Cu) vicinal surfaces, i.e., surface energy, step energy, kink energy and electronic interactions between steps, is studied at 0K from electronic structure calculations in the tight-binding approximation using a s, p and d valence orbital basis set. Then, the surface phonon spectra of copper are investigated in the harmonic approximation with the help of a semi-empirical inter-atomic potential. This allows to derive the contribution of phonons at finite temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…In Section 1 of the Supporting Information, we elaborate further on this issue and provide a detailed discussion of why linear fitting approaches to surface energy estimation should be avoided in materials like TiO 2 rutile where surface-surface interactions are strong. Alongside this obvious practical limitation, we also argue that using a linear fitting approach in this context has some questionable underlying assumptions because it fails to properly recognize surface energy oscillations in TiO 2 rutile as a non-random, 44 , and direct extraction of step energies from vicinal slabs 45,46 , where, in all cases, it was ensured that total surface energies were fully converged at the slab thicknesses used. The difficulty with systems like TiO 2 rutile is that linear fitting techniques do not work, and neither does the "brute force" approach of using arbitrarily large slabs because of the very long-ranged nature of surface-surface interactions.…”
Section: 3mentioning
confidence: 99%
“…In Section 1 of the Supporting Information, we elaborate further on this issue and provide a detailed discussion of why linear fitting approaches to surface energy estimation should be avoided in materials like TiO 2 rutile where surface-surface interactions are strong. Alongside this obvious practical limitation, we also argue that using a linear fitting approach in this context has some questionable underlying assumptions because it fails to properly recognize surface energy oscillations in TiO 2 rutile as a non-random, 44 , and direct extraction of step energies from vicinal slabs 45,46 , where, in all cases, it was ensured that total surface energies were fully converged at the slab thicknesses used. The difficulty with systems like TiO 2 rutile is that linear fitting techniques do not work, and neither does the "brute force" approach of using arbitrarily large slabs because of the very long-ranged nature of surface-surface interactions.…”
Section: 3mentioning
confidence: 99%
“…26 The numbers n s ͑p͒ and n s ͑ϱ͒ are the total number of bonds in the sth coordination sphere broken by the vicinal and flat surfaces, respectively. Due to the short range of the EPP parameters, n step,s becomes a constant as soon as p overcomes a value p ϱ , which is usually very small: most often, according to Vitos et al, 21 p ϱ = 2.…”
Section: Step Energiesmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For example, Methfessel et al, 11 employing the full-potential linear muffin-tin orbital ͑FP-LMTO͒ method, found a roughly parabolic behavior for the surface energy of the low-Miller-index ͑flat͒ surfaces across the 4d transition-metal series, which was explained in terms of the d-band occupation. Almost at the same time, Skriver and Rosengaard, 12 employing a Green's-function technique based on the LMTO method, discussed the trends exhibited by the surface energies of flat surfaces of the alkali, alkaline earth, divalent rare-earth, 3d, 4d, and 5d transition and noble metals, as derived from the surface tension of liquid metals.…”
Section: Introductionmentioning
confidence: 99%
“…When the steps are close together, the number of allowed configurations are reduced, and this reduction of entropy is equivalent to a step repulsion. Steps interact also electronically through the modification of the density of states 3,4 , electrostatic ally due to the presence of electrostatic dipoles at the steps 5,6 , and thermally through the modification of their vibrational free energy 7 . They also interact elastically through the long range relaxation fields generated by local atomic relaxations at the steps 8 .…”
Section: Introductionmentioning
confidence: 99%